The Effect of Manual Resources Implementation on Starbucks Coffee District 39 Barista Performance - Regina; Mulyati Mulyati; Nurlaila Mashabi (Family Welfare Education, 2021)
This study aims to analyze the effect of manual resources implementation on the performance of Starbucks Coffee district 39 baristas. The method used in this study is quantitative associative. The location of this research was conducted at Starbucks Coffee district 39, from June to July 2021. Respondents in the study were selected using purposive sampling technique. Respondents in this study involved 54 employees at Starbucks Coffee district 39.The questionnaire used in this study uses a Likert scale which is used to measure attitudes, opinions and perceptions of a person or group of people tending to social phenomena (Sugiyono, 2013). The data that has been collected was analyzed using simple linear regression analysis. Based on the results of the calculated regression equation, it shows that the rxy〗_count Manual resources on Barista Performance is 0.959 with the number of samples (N) 54, then the rxy〗_table is 0.262. So it shows rxy〗_count > rxy〗_table or 0.959 > 0.262. The results of the t-test with a significant level of 0.05 obtained t(count) > t_table which is 24.40 > 0.226 from manual resourceson barista performance. The conclusion obtained from the correlation between Manual resourcesand Barista Performance has a unidirectional relationship which states that if Manual resourcesincreases, the barista's performance will also increase. The results of the Pearson Product Moment correlation are based on coefficient intervals, at the level of the relationship between the two variables, which is very strong.Keywords: Barista, Performance, SOP, Manual Resources